Biomedical Applications of DNA‐Based Hydrogels. (11th November 2019) - Gačanin, Jasmina; Synatschke, Christopher V.; Weil, Tanja
Abstract: Nucleic acids are gaining significant attention as versatile building blocks for the next generation of soft materials. Due to significant advances in the chemical synthesis and biotechnological production, DNA becomes more widely available enabling its usage as bulk material in various applications. This has prompted researchers to actively explore the unique features offered by DNA‐containing materials like hydrogels. In this review article, recent developments in the field of hydrogels that feature DNA as a component either in the construction of the material or as functional unit within the construct and their biomedical applications are discussed in detail. First, different synthetic approaches for obtaining DNA hydrogels are summarized, which allows classification of DNA materials according to their structure. Then, new concepts, properties, and applications are highlighted such as DNA‐based biosensor devices, drug delivery platforms, and cell scaffolds. With the 2018 Nobel Prize in Physiology or Medicine being awarded to cancer immunotherapy underscoring the importance of this therapy, DNA hydrogel systems designed to modulate the immune system are introduced. This review aims to give the reader a timely overview of the most important and recent developments in this emerging class of therapeutically useful materials of DNA‐based hydrogels. Abstract : DNA hydrogels are an emerging class of soft materials with great potential in biomedical applications. DNA offers unprecedented levels of programmability, enabling precise assembly of its constituent building blocks. Due to reversible interactions between complementary DNA strands, highly dynamic and bioactive materials can be constructed. They are explored as biosensors, drug delivery systems, cellular scaffolds, and for immunotherapy.